Analysis of Legal Protection of the Fulfillment of the Right to Obtain Employment for Persons with Disabilities - Sitabuana, Tundjung Herning; Octavia S, Christine (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
The right to get the opportunity to work is not an easy thing for persons with disabilities to obtain. Because, there is discrimination that can be seen in some of the requirements or criteria for the workforce needed. One-eyed view of people with disabilities because it is assumed that the work they do will not be as maximal as if it were done by normal workers. This is certainly interesting to study how legal protection is in fulfilling the right to work for persons with disabilities. This research uses a normative method by collecting secondary data consisting of primary legal materials, namely examining a statutory regulation related to research such as the Constitution of the Republic of Indonesia, Law Number 13 of 2003 concerning Manpower, and Law Number 8 of 2016 concerning Persons with Disabilities, then secondary legal materials, namely using books, journals, and the internet, as well as tertiary legal materials, namely using dictionaries. This research is based on written rules relating to legal protection in terms of fulfilling the right to work for persons with disabilities. The results of this study, that persons with disabilities get legal protection in obtaining jobs listed in several articles, namely Article 67 paragraph (1) of the Labor Law and Article 14 of Law Number 4 of 1997 concerning Persons with Disabilities. Then, with this research it is hoped that it can become material for the government's evaluation so that the government can pay more attention to the rights of persons with disabilities, especially in terms of getting employment opportunities.